Kesediaan Membayar Pengunjung untuk Konservasi Kawasan Hutan Air Terjun Benang Kelambu Lombok Ditinjau dari Perspektif Islam - Moh. Huzaini; Ali Akbar Hidayat; Muhamad Baiul Hak (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research aims to identify factors that influence visitors' willingness to pay for conservation activities in the Benang Kelambu Waterfallforest area from an Islamic perspective. This type of research is associative research with a quantitative approach. The research location was carried out in the Rinjani forest area (RTK1) which contains the Benang Stokel waterfall and the Benang Kelambu waterfall, which are administratively included in Aik Berik Village, North Batukliang District, Central Lombok Regency, West Nusa Tenggara. The research sample was taken using Non-Probability Sampling, and respondents were selected using a purposive sampling technique with a sample size of 160 respondents. The variables used in the research are religiosity, age, gender, income, education level, awareness, perception, and willingness to pay. The results of this research show that partially the variables age, income, awareness of the importance of conservation, religiosity, and gender have a significant effect on willingness to pay, while the variables education and perception of the availability of facilities have an effect but are not significant. Meanwhile, simultaneously all variables have an influence and are significant on the amount of willingness to pay for conservation